Method for improving fatigue performance of TiAl alloy

The whole-sheet structure is formed through thermal isostatic pressure and laser shot peening treatment, which solves the problem of poor fatigue performance of TiAl alloy, significantly improves its fatigue resistance and meets the application needs in the aviation field.

CN119121088APending Publication Date: 2024-12-13JIANGSU HAOJING INTELLIGENT MFG TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311856577.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The application of TiAl alloy in aviation and other fields is limited by its poor room temperature plasticity, high temperature creep resistance, oxidation resistance and fatigue performance, especially fatigue performance is one of the main reasons for the failure of aircraft engine components.

Method used

After the whole sheet layer structure is formed, the TiAl alloy ingot is heat treated and polished under an argon atmosphere, the laser shot peening is followed by laser shot peening, and the residual compressive stress is introduced by the shock wave formed by laser shot peening to increase the Fatigue resistance of the material.

Benefits of technology

It significantly improves the fatigue performance of TiAl alloy, inhibits crack propagation, extends the life of the material, and meets the application needs in the aviation field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121088A_ABST
    Figure CN119121088A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving the fatigue performance of a TiAl alloy, and belongs to the technical field of alloy additive manufacturing. The method comprises the following steps: carrying out hot isostatic pressing treatment on a TiAl alloy cast ingot to obtain a TiAl alloy sample; the TiAl alloy sample is subjected to heat treatment, grinding and polishing in the argon atmosphere, and a TiAl alloy sample of a full lamellar structure is obtained; according to the method, the TiAl alloy sample with the full lamellar structure is subjected to laser shot peening treatment, the fatigue performance of the TiAl alloy can be effectively improved through the method, crack propagation of the TiAl alloy is inhibited, and the application requirement is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of alloy additive manufacturing, and in particular relates to a method for improving fatigue performance of TiAl alloy. Background Art

[0002] TiAl intermetallic compounds have the characteristics of high specific strength, light weight, corrosion resistance, excellent high-temperature mechanical properties, and high oxidation resistance. The operating temperature can reach 700-1000℃. It is a lightweight high-temperature structural material with great application prospects. It can be widely used in cutting-edge frontier fields such as aerospace industry and automobile industry (such as low-pressure turbine blades of aircraft engines, automobile supercharger turbines, etc.). However, the room temperature plasticity, high-temperature creep resistance, oxidation resistance and fatigue properties of TiAl alloys are poor, which limits the further application of TiAl alloys in aviation and other fields. In particular, fatigue performance is one of the main reasons for the failure of aircraft engine components. Fatigue refers to the phenomenon that materials, parts and components gradually produce local permanent performance changes at a certain point or certain points under cyclic loads, form cracks after a certain number of cycles, and expand under the action of load until they are completely broken.

[0003] At present, most alloying methods are used to improve the strength of TiAl alloys and thus improve fatigue performance. For example, the high-temperature mechanical properties of TiAl alloys are improved by adding the alloying element Nb. However, the fatigue performance of TiAl alloys formed by this method is still poor and prone to fracture, which cannot meet application requirements. Secondly, surface heat treatments such as surface quenching, surface carburizing, and surface nitriding are also used to improve the fatigue strength of materials. However, for some notched materials, these methods will increase the sensitivity of the notch, which will lead to a decrease in the fatigue strength of the material. Therefore, it is necessary to propose a new method to meet the requirements of improving the fatigue strength of different materials. Summary of the invention

[0004] The present disclosure aims to solve at least one of the technical problems existing in the prior art and provide a method for improving the fatigue performance of TiAl alloy.

[0005] The present disclosure provides a method for improving fatigue performance of TiAl alloy, the method comprising:

[0006] The TiAl alloy ingot is subjected to hot isostatic pressing to obtain a TiAl alloy sample;

[0007] The TiAl alloy sample is heat treated, ground and polished in an argon atmosphere to obtain a TiAl alloy sample with a full lamellar structure;

[0008] The TiAl alloy specimens with full lamellar structure were subjected to laser shot peening.

[0009] Optionally, the wavelength of the laser shot peening treatment is 530-1100nm, and the laser intensity is 6-12GW / cm 2 , pulse time is 5-7ns, and spot diameter is 1-2mm.

[0010] Optionally, the laser intensity of the laser shot peening is 6W / cm 2 .

[0011] Optionally, during the laser shot peening process, a thin water layer is used as the constraining layer, and a black PVC tape, black paint or aluminum foil is used as the sacrificial layer.

[0012] Optionally, the laser shot peening treatment of the TiAl alloy sample with full lamellar structure comprises:

[0013] The whole-layer TiAl alloy sample is subjected to single-point laser shot peening, and then the TiAl alloy sample after single-point shot peening is subjected to laser shot peening treatment at least once with a spot overlap rate of 30-40%.

[0014] Optionally, the hot isostatic pressing treatment is performed at a temperature of 1200-1300° C., a time of 3-5 h, and a pressure of 120-160 MPa.

[0015] Optionally, the heat treatment temperature is 1300-1400° C., the time is 20-25 hours, and the cooling method is furnace cooling.

[0016] Optionally, the full lamellar structure size of the TiAl alloy sample is 30-80 μm.

[0017] Optionally, the TiAl alloy ingot is a high Nb-TiAl alloy ingot.

[0018] Optionally, the TiAl alloy ingot is a Ti-45Al-8.5Nb-0.2W-0.2B-0.02Y alloy ingot.

[0019] The present disclosure provides a method for improving the fatigue performance of TiAl alloy, the method comprising: performing hot isostatic pressing on a TiAl alloy ingot to obtain a TiAl alloy sample; performing heat treatment, grinding, and polishing on the TiAl alloy sample in an argon atmosphere to obtain a TiAl alloy sample with a full lamellar structure; and performing laser shot peening on the TiAl alloy sample with a full lamellar structure. This method can effectively improve the fatigue performance of the TiAl alloy, inhibit the crack propagation of the TiAl alloy, and meet application requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A flowchart of a method for improving fatigue performance of TiAl alloy according to an embodiment of the present disclosure;

[0021] Figure 2 is a surface structure diagram of the TiAl alloy sample after hot isostatic pressing treatment in Example 1 of the present disclosure; wherein, Figure 2 (a) is a FESEM image at 100 times magnification;

[0022] Figure 2 (b) is a FESEM image at 1000 times magnification; Figure 2 (c) is a FESEM image at 1000 times magnification; Figure 2 (d) is a FESEM image at 2000 times magnification;

[0023] Figure 3 is a surface structure diagram of the TiAl alloy sample after heat treatment of Example 1 of the present disclosure; wherein, Figure 3 (a) is a FESEM image at 300 times magnification; Figure 3 (b) is a FESEM image at 400 times magnification; Figure 3 (c) is a FESEM image at 500 times magnification; Figure 3 (d) is a FESEM image at 1000 times magnification;

[0024] Figure 4 The residual stress distribution result of the TiAl alloy sample of Example 1 of the present disclosure is shown in FIG. Figure 4 (a) is the untreated sample; Figure 4 (b) is 6GW / cm 2 Intensity of the specimen after laser shot peening; Figure 4 (c) is 12GW / cm 2 Intensity of the specimen after laser shot peening; Figure 4 (d) is the location of the principal stress and shear stress;

[0025] Figure 5 The cross-sectional hardness test result of the TiAl alloy sample of Example 1 of the present disclosure;

[0026] Figure 6 SN curves at room temperature of the full lamellar TiAl alloy samples of Example 1 and Comparative Example 1 of the present disclosure. DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the present disclosure is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the described embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.

[0028] like Figure 1As shown, the present disclosure provides a method S100 for improving fatigue performance of TiAl alloy, which specifically includes the following steps S110 to S130:

[0029] S110, performing hot isostatic pressing on the TiAl alloy ingot to obtain a TiAl alloy sample;

[0030] Specifically, Ti powder, Al powder and other powders (such as Nb, W, Cr, Y, etc.) are selected, melted into liquid form and introduced into a casting mold, and after cooling and solidification, a TiAl alloy ingot is prepared. Afterwards, the formed TiAl alloy ingot is subjected to hot isostatic pressing at a temperature of 1200-1300°C, a time of 3-5h, and a pressure of 120-160MPa to reduce the porosity of the TiAl alloy and obtain a dense TiAl alloy ingot, and then several TiAl alloy samples are cut from the TiAl alloy ingot.

[0031] In step S110, the TiAl alloy ingot may be a high Nb-TiAl ingot, for example, a Ti-45Al-8.5Nb-0.2W-0.2B-0.02Y alloy ingot.

[0032] S120, heat treating, grinding, and polishing the TiAl alloy sample in an argon atmosphere to obtain a TiAl alloy sample with a full lamellar structure;

[0033] Specifically, the TiAl alloy sample was sealed with argon gas, and the sealed sample was subjected to full-layer heat treatment at a temperature of 1300-1400°C for 20-25 hours, followed by furnace cooling. Then, multiple 12.5×14.3×3mm 3 The sample size is 12.5×14.3mm. 2 The surface of the TiAl alloy sample was polished to 2000 grit SiC with different sandpapers. Then the sample was polished with colloidal SiO2 polishing liquid with a particle size of 0.05 μm until there was no scratch on the surface of the TiAl alloy sample.

[0034] It should be noted that, in this embodiment, mechanical polishing or electrolytic polishing may be used to reduce the roughness of the alloy surface.

[0035] In other preferred embodiments, the full lamellar structure size of the TiAl alloy sample is 30-80 μm. This small-sized full lamellar structure can effectively improve the mechanical properties of the sample.

[0036] In this embodiment, a TiAl alloy with a full lamellar structure is formed by heat treating a TiAl alloy sample. The full lamellar structure is beneficial for improving the fatigue performance of the TiAl alloy material.

[0037] S130. Laser shot peening is performed on the TiAl alloy sample with full lamellar structure.

[0038] Specifically, the TiAl alloy sample obtained in step S120 is subjected to single-point laser shot peening, and then the TiAl alloy sample after single-point shot peening is subjected to laser shot peening treatment at least once with a spot overlap rate of 30-40%, for example, 1-3 times, wherein the wavelength of the laser shot peening treatment is 530-1100nm, and the laser intensity is 6-12GW / cm 2 , pulse time is 5-7ns, spot diameter is 1-2mm, peak stress is 5-5.5Gpa, and spot overlap rate is 33%.

[0039] In some preferred embodiments, the wavelength of laser peening is 1064 nm and the laser intensity is 6 W / cm 2 .

[0040] In other preferred embodiments, the wavelength of laser shot peening is 532 nm and the laser intensity is 12 W / cm 2 .

[0041] Furthermore, in this embodiment, the constrained layer is made of water, which can prevent the plasma generated by the laser shock from leaving the material surface, thereby causing more laser energy to be transmitted to the target metal in the form of shock waves to produce a higher order of magnitude of shock wave intensity. At the same time, water as a liquid medium can also adapt to the surfaces of parts with various curvatures.

[0042] It should be noted that the constrained layer of this embodiment is achieved by using a water jet, and the jet is located above the laser target position to ensure that a smooth laminar water flow is formed in the area to be laser treated.

[0043] Furthermore, in this embodiment, the sacrificial layer is made of black PVC tape, black paint or aluminum foil to protect the target metal surface through the sacrificial layer to prevent the target metal surface from being ablated and melted by the laser, which can also further enhance the intensity of the shock wave.

[0044] In some preferred embodiments, the sacrificial layer may be made of black PVC tape, and three layers of black PVC tape may be used to prevent the thermal effect from causing small holes in the PVC tape, which in turn may cause the thermal effect to penetrate the small holes and damage the metal surface.

[0045] In this embodiment, a short-pulse, high-peak laser is used to irradiate the alloy surface, and a large amount of plasma is formed on the alloy surface by impacting the sacrificial coating on the alloy surface. The force effect of the shock wave is utilized to cause yielding and cold plastic deformation on the material surface, and beneficial residual compressive stress is generated in the deformation area, thereby improving the fatigue resistance and wear resistance of the TiAl alloy material.

[0046] In this embodiment, through the coordinated treatment of hot isostatic pressing, heat treatment and laser shot peening, the fatigue performance of the TiAl alloy surface is significantly improved, and the hardness of the alloy is also improved.

[0047] The method for improving the fatigue performance of TiAl alloy will be further described below in conjunction with specific embodiments:

[0048] Example 1

[0049] The method for improving the fatigue performance of TiAl alloy in this example includes the following steps:

[0050] S1. Select Ti-45Al-8.5Nb-0.2W-0.2B-0.02Y alloy ingot, and hot isostatically press the alloy ingot at 1250℃ and 150MPa for 4h to reduce the porosity of the ingot. Then, cut several 20×20×15mm 3 Rectangular specimen of size.

[0051] Furthermore, in this embodiment, the surface structure of the sample after hot isostatic pressing was observed using a backscattering pattern on a field emission scanning electron microscope, and the results are as follows: Figure 2 As shown, it can be seen that the structure after hot isostatic pressing is a near-lamellar structure, which is mainly composed of lamellar clusters of about 8μm and γ phase and B2 phase distributed between the lamellar clusters.

[0052] It should be understood that the B2 phase is a brittle phase. When the B2 phase exists, the mechanical properties of the corresponding specimens are poor, which is not conducive to improving fatigue performance.

[0053] S2. The cut TiAl alloy sample was sealed in an argon atmosphere, and the sealed sample was kept at 1340°C for 24 hours, and then cooled in the furnace to obtain a TiAl alloy sample with full lamellar structure. The heat-treated TiAl alloy sample was 20×20 mm 2 The surface is ground to 2000 grit SiC.

[0054] Furthermore, this embodiment also observes the backscattering pattern of the sample surface structure after heat treatment using a field emission scanning electron microscope, and the results are as follows: Figure 3 As shown, it can be seen that after heat treatment, a full lamellar structure is formed, the average size of the lamellar is about 60μm, and the B2 phase is completely eliminated, which is beneficial to improving the mechanical properties of the sample.

[0055] S3. Laser shot peening was performed on the TiAl alloy sample with full lamellar structure. The process parameters of laser shot peening were as follows: wavelength of 532nm, spot size of 1.5mm, pulse duration of 5.7ns, sacrificial layer of 3 layers of PVC tape, constraint layer of thin water layer, spot overlap rate of 33%, and laser intensity of 6GW / cm 2 and 12GW / cm 2 The two power intensities are compared and analyzed.

[0056] Furthermore, this embodiment also tests the surface of the untreated original TiAl alloy sample and the 6GW / cm 2 and 12GW / cm 2 The distribution of residual stress was tested by incremental drilling on the surface of TiAl alloy specimens treated with laser shot peening. The results are shown in Figure 4 As shown in the figure, the surface of the untreated sample has a tensile stress of about 400 MPa. This tensile stress may be caused by putting sandpaper on the polishing machine to polish the surface of the sample. 2 and 12GW / cm 2 The samples treated with laser shot peening were subjected to residual compressive stress, and the depth of residual stress was about 1000-1200 μm, among which 6 GW / cm 2 The surface residual compressive stress of the sample treated by laser shot peening is about 500MPa; 12GW / cm 2 For the sample treated with high-intensity laser shot peening, the magnitude of the surface residual compressive stress introduced is about 1100MPa. It is worth noting that the residual compressive stress introduced by laser shot peening is compressive stress, which is beneficial to improving the fatigue performance of the alloy.

[0057] Furthermore, this embodiment also tests the surface of the untreated original TiAl alloy sample and the 6GW / cm 2 and 12GW / cm 2 The hardness of the TiAl alloy sample surface treated by laser shot peening was measured. Figure 5 As shown, after 12GW / cm 2 and 6GW / cm 2 After high-intensity laser shot peening treatment, the surface hardness of TiAl alloy samples was significantly improved, 6GW / cm 2 The surface hardness of the sample after laser shot peening is increased by about 33%, 12GW / cm 2 The effect of improving the surface hardness is about 40%. In addition, 6GW / cm 2 Laser peening achieves better cross-sectional hardness distribution, 6GW / cm 2 The depth of the hardness gradient caused by laser peening is about 600μm, 12GW / cm2 The depth of the hardness gradient caused by laser peening is about 400 μm.

[0058] Furthermore, in this embodiment, high cycle fatigue tests were performed on the untreated original TiAl alloy sample and the treated TiAl alloy sample using four-point bending fatigue. The results are shown in Tables 1 and 2, and the above data were respectively plotted into stress cycle curves (SN curves) of wind power ductile iron castings. The SN curve is a relationship curve between stress S and fatigue life N obtained based on the fatigue strength experimental data of the material, as shown in Figure 6 shown.

[0059] Among them, the SN curve reflects the high cycle fatigue life of wind power ductile iron castings under different stresses. According to Table 1 and Figure 6 The results show that for the original high Nb-TiAl alloy, the fatigue life (SN) curve shows a continuous downward trend in the load range of 320-240MPa. In this region, as the load applied to the sample decreases, the fatigue life gradually increases, proving that the life of the material in this region is greatly affected by external forces. When the load is 240PMa, the corresponding fatigue life is 10 7 Since this point is in the flat zone, even if the force is increased slightly, the life will be sharply reduced to 10 7 Below that, that is, when the load is 260MPa or higher, the TiAl alloy breaks. Therefore, it can be considered that 240MPa is the fatigue limit of the original high Nb-TiAl alloy.

[0060] Secondly, according to Table 2 and Figure 6 As shown in the figure, for the high Nb-TiAl alloy treated by the method of this embodiment, the fatigue life (SN) curve is a continuous downward trend in the load range of 300-260MPa. In this region, as the load applied to the sample decreases, the fatigue life gradually increases, proving that the life of the material in this region is greatly affected by external forces. When the load is 260PMa, the corresponding fatigue life is 10 7 Therefore, it can be considered that 260 MPa is the fatigue limit of the high Nb-TiAl alloy after laser shot peening.

[0061] In summary, by comparing the original high Nb-TiAl alloy sample with the treated high Nb-TiAl alloy sample, it can be seen that the fatigue limit of the sample treated by the method of this embodiment is improved, and the maximum load is increased from the original 240MPa to 260MPa, that is, the sample treated by the method of this embodiment can achieve a cycle number of more than 5000000 under the load of 240MPa and 260MPa. Of course, it can be seen from Table 1 and Table 2 that under other loads, relative to the untreated TiAl alloy sample, the cycle number of the TiAl alloy sample treated by this embodiment is also improved. For example, under a load of 300MPa, the maximum number of cycles of the original high Nb-TiAl alloy is 203280 times, that is, after the above number of cycles, the original TiAl alloy breaks, and the maximum number of cycles of the treated Nb-TiAl alloy is 249328 times, that is, after the above number of cycles, the treated TiAl alloy sample breaks.

[0062] Table 1 High cycle life fatigue data of original high Nb-TiAl alloy

[0063]

[0064]

[0065] Table 2 High cycle fatigue life data of high Nb-TiAl alloy after treatment

[0066] Sample No. Stress / MPa Lifespan / times 1 320 152230 2 320 167660 3 300 249328 4 300 167540 5 300 237588 6 280 554135 7 280 589610 8 260 5000000 not broken 9 260 5000000 not broken 10 240 5000000 not broken

[0067] The present disclosure proposes a method for improving the fatigue performance of TiAl alloy, which has the following beneficial effects compared with the prior art: by co-processing hot isostatic pressing, heat treatment and laser shot peening, a TiAl alloy specimen with a full lamellar structure is formed, which effectively improves the fatigue performance and hardness of the TiAl alloy and meets the application requirements in the aviation field.

[0068] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present disclosure, but the present disclosure is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and substance of the present disclosure, and these modifications and improvements are also considered to be within the scope of protection of the present disclosure.

Claims

1. A method for improving the fatigue performance of TiAl alloy, characterized in that: The method comprises: The TiAl alloy ingot is subjected to hot isostatic pressing to obtain a TiAl alloy sample; The TiAl alloy sample is heat treated, ground and polished in an argon atmosphere to obtain a TiAl alloy sample with a full lamellar structure; The TiAl alloy specimens with full lamellar structure were subjected to laser shot peening.

2. The method according to claim 1, characterized in that The wavelength of the laser shot peening treatment is 530-1100nm, and the laser intensity is 6-12GW / cm 2 , pulse time is 5-7ns, and spot diameter is 1-2mm.

3. The method according to claim 2, characterized in that The laser intensity of the laser shot peening process is 6W / cm 2 .

4. The method according to claim 1, characterized in that: The constraining layer of the laser shot peening process is a thin water layer, and the sacrificial layer is a black PVC tape, black paint or aluminum foil.

5. The method according to claim 1, characterized in that The laser shot peening treatment of the TiAl alloy sample with full lamellar structure comprises: The whole-layer TiAl alloy sample is subjected to single-point laser shot peening, and then the TiAl alloy sample after single-point shot peening is subjected to laser shot peening treatment at least once with a spot overlap rate of 30-40%.

6. The method according to claim 1, characterized in that The hot isostatic pressing treatment is performed at a temperature of 1200-1300° C., for 3-5 hours, and at a pressure of 120-160 MPa.

7. The method according to claim 1, characterized in that The heat treatment temperature is 1300-1400° C., the time is 20-25 hours, and the cooling method is furnace cooling or solution cooling.

8. The method according to claim 1, characterized in that The full lamellar structure size of the TiAl alloy sample is 30-80 μm.

9. The method according to claim 1, characterized in that: The TiAl alloy ingot is a high Nb-TiAl alloy ingot.

10. The method according to claim 1, characterized in that The TiAl alloy ingot is a Ti-45Al-8.5Nb-0.2W-0.2B-0.02Y alloy ingot.

Citation Information

Cited By

  • A method for improving high-temperature high-cycle fatigue performance of TiAl alloy through pre-oxidation

    CN122918478A